Comparison of rat and rabbit embryo–fetal developmental toxicity data for 379 pharmaceuticals: on the nature and severity of developmental effects. (25th November 2016) - Theunissen, Peter T.; Beken, Sonja; Beyer, Bruce K.; Breslin, William J.; Cappon, Gregg D.; Chen, Connie L.; Chmielewski, Gary; De Schaepdrijver, Luc; Enright, Brian; Foreman, Jennifer E.; Harrouk, Wafa; Hew, Kok-Wah; et al.
Abstract: Regulatory non-clinical safety testing of human pharmaceuticals typically requires embryo–fetal developmental toxicity (EFDT) testing in two species (one rodent and one non-rodent). The question has been raised whether under some conditions EFDT testing could be limited to one species, or whether the testing in a second species could be decided on a case-by-case basis. As part of a consortium initiative, we built and queried a database of 379 compounds with EFDT studies (in both rat and rabbit animal models) conducted for marketed and non-marketed pharmaceuticals for their potential for adverse developmental and maternal outcomes, including EFDT incidence and the nature and severity of adverse findings. Manifestation of EFDT in either one or both species was demonstrated for 282 compounds (74%). EFDT was detected in only one species (rat or rabbit) in almost a third (31%, 118 compounds), with 58% (68 compounds) of rat studies and 42% (50 compounds) of rabbit studies identifying an EFDT signal. For 24 compounds (6%), fetal malformations were observed in one species (rat or rabbit) in the absence of any EFDT in the second species. In general, growth retardation, fetal variations, and malformations were more prominent in the rat, whereas embryo–fetal death was observed more often in the rabbit. Discordance across species may be attributed to factors such as maternal toxicity, study design differences, pharmacokinetic differences, and pharmacologic relevance of species. The current analysis suggests that in general both species are equally sensitive on the basis of an overall EFDT LOAEL comparison, but selective EFDT toxicity in one species is not uncommon. Also, there appear to be species differences in the prevalence of various EFDT manifestations (i.e. embryo–fetal death, growth retardation, and dysmorphogenesis) between rat and rabbit, suggesting that the use of both species has a higher probability of detecting developmental toxicants than either one alone.